Stable price level and changing prices - Antti Suvanto; Juhana Hukkinen (Bank of Finland, 2004)
The paper investigates the relationship between relative price movements and changes in the aggregate price level using monthly data on Finland's Consumer Price Index and its components from the period covering the past eight and a half years.This was a period of very low inflation.The rate of growth in the aggregate price level was occasionally very close to zero.The paper shows that declining nominal prices were a rather common phenomenon during this period of low or no inflation.The declining prices cannot, however, be explained by lack of demand or any generalized deflationary tendencies.Hence, the downward rigidity of nominal prices has not prevented relative price adjustments under price stability.The paper develops a new method for looking at the composition of inflation and illustrating how relative price dynamics interact with changes in the aggregate price level.The correlation of relative price variability and aggregate inflation has been negligible, but the correlation between the skewness of price change distribution and aggregate inflation is high.This is in accordance with the predictions of the menu cost models.A significant proportion of the relative price changes appear to have been persistent, suggesting the dominance of productivity and other supply shocks.
URN:NBN:fi:bof-20140807605
Keywords: E31; 330; price level; inflation; deflation; prices; business cycles